Female entrepreneurs in the Indian informal service sector: a study based on Leibenstein's approach. (2015) - Sengupta, Atanu; Datta, Soumyendra Kishore; Mondal, Susanta
This study focuses on the performance differences between male and female entrepreneurs in the informal service sector in India. For this the National Sample Survey Organisation (NSSO) unit level data has been used. It captures the pattern of entrepreneurial activity, socio-economic status of entrepreneurs; nature of problem faced by female entrepreneur's vis-à-vis the male entrepreneurship. Performance of male and female entrepreneurs has been analysed in terms of X-efficiency as developed by Leibenstein. In both the traditional sector and modern sector, female entrepreneurs outperform the male entrepreneurs. However, they emerge to be more efficient in the commercial enterprises. Influences of different factors explaining such differences in performance have also been examined.